The effect and nature of N–H complexes in the control of the dominant photoluminescence transitions in UV-hydrogenated GaInNAs. Issue 41 (11th May 2017) - Brown, C. R.; Estes, N. J.; Whiteside, V. R.; Wang, B.; Hossain, K.; Golding, T. D.; Leroux, M.; Al Khalfioui, M.; Tischler, J. G.; Ellis, C. T.; Glaser, E. R.; Sellers, I. R.
Abstract : A study of certain defects in GaInNAs, and their passivation. The passivation process could lead to more efficient photovoltaic devices. Abstract : Due to its 1 eV band gap and GaAs-matched lattice constant, GaInNAs has long been considered for use in four-junction multi-junction solar cells; but, material quality issues have impeded its use in highly efficient devices. Here, we present an analysis of GaInNAs samples partially hydrogenated via a UV-activated process in which nitrogen-related alloy fluctuations, impurities, and defects have been passivated; remarkably, removing completely the 's-shape' dependence of the photoluminescence while keeping intact the effects of nitrogen substitution, i.e., the band gap of the alloy prior to passivation. Hydrogenation of the optical samples by a UV-activated process has resulted in GaInNAs photoluminescence dominated by the free-excitonic band gap transition, rather than radiative recombination processes from the shallow localized centers that result due to unavoidable alloy fluctuations. This behavior is unique since these centers dominate the low temperature photoluminescence even in the highest quality dilute nitrides. Density functional theory calculations show that the hydrogenation of the N and Ga atoms eliminates the defect levels from the band gap through the formation of H–N centers that act as donors; while at high concentration of hydrogen, Ga–H2 –N complexes reside within the continuum. The formation of these hydrogen complexes, along with the incumbent change of the band structure, explains the reduction of emission from the localized centers upon hydrogenation.